IN VITRO EVALUATION OF ANTI-AGING ACTIVITIES OF ARTOCARPUS LAKOOCHA HEARTWOOD EXTRACT - Tengamnuay, P.; Prugsakij, W.; Wongkajornsilp, A. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Artocarpus lakoocha heartwood extract (Family Moraceae) and its main active constituent oxyresveratrol are potent tyrosinase inhibitors. Recently we have shown that the extract lightened the skin in volunteers and possesses several ROS scavenging activities [1, 2]. In this study we evaluated A. lakoocha heartwood extract and oxyresveratrol for their anti-aging activities in cultured fibroblasts. Using the MTT assay, the proliferative effect of A. lakoocha extract and that of oxyresveratrol was similar to the one of epigallocatechin gallate, french pine bark extract, L-ascorbic acid and Trolox® in the same concentration range (25 – 100 µg/ml). All the test antioxidants were also capable of protecting the fibroblasts against cell damages caused by hydrogen peroxide and UV-A radiation. Based on the extent of the LDH release from the fibroblasts, A. lakoocha, oxyresveratrol, pine bark and Trolox® caused less membrane irritation than L-ascorbic acid and EGCG when compared at the same concentration (100µg/ml). A. lakoocha and oxyresveratrol also showed a good anti-collagenase activity, with the respective mean IC50 of 58.8 and 153.1 µg/mL, which were less potent than EGCG (8.0 µg/mL) and pine bark (21.9 µg/mL) but much more potent than L-ascorbic acid (1.331 mg/mL) and Trolox® (2.348 mg/mL). Moreover, both A. lakoocha and oxyresveratrol could reduce the extent of DNA damages caused by UV-A as detected by flow cytometry. In conclusion, the multi-functional beneficial effects of A. lakoocha heartwood extract may have a strong potential for the use in cosmetic and other health-related products. Acknowledgements: National Research Council of Thailand provided funding.